2004
DOI: 10.1080/1385404049052409
|View full text |Cite
|
Sign up to set email alerts
|

The Rey AVLT Serial Position Effect: A Useful Indicator of Symptom Exaggeration?

Abstract: This investigation explored the usefulness of serial position patterns during word recall on the Rey Auditory Verbal Learning Test (RAVLT; Rey, 1964) as an indicator of poor effort. Significantly better recall for early (primacy) and recent (recency) material defines the serial position effect (SPE; Rundus, 1971). The SPE on the RAVLT was examined in four groups: normal controls (NC), symptom-coached simulators (SC), test-coached simulators (TC), and a group of moderate to severe subacute traumatic brain injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(54 reference statements)
4
4
0
Order By: Relevance
“…Consistent with previous reports (Suhr, 2002; Sullivan et al, 2002; Powell et al, 2004), primacy/recency ratios were abnormal ( p < 0.05) in 60% of the simulated malingerers and 20% of the abnormal controls.…”
Section: Results: Experimentssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous reports (Suhr, 2002; Sullivan et al, 2002; Powell et al, 2004), primacy/recency ratios were abnormal ( p < 0.05) in 60% of the simulated malingerers and 20% of the abnormal controls.…”
Section: Results: Experimentssupporting
confidence: 91%
“…Consistent with prior studies (Suhr, 2002; Powell et al, 2004; Gavett and Horwitz, 2012; Egli et al, 2014), we found strong primacy and recency effects on initial list presentations (A1 and B) that diminished with learning. Recency effects were absent on recall, consistent with suggestions that recency effects depend on access to a short-term buffer that is overwritten by the presentation of competing lists (Davelaar et al, 2005).…”
Section: Experiments 1 Discussionsupporting
confidence: 91%
“…For example, several investigators have explored the utility of Trail Making Test (TMT; Reitan & Wolfson, 1992) scores as indicators of suboptimal effort in patient and non-patient populations (Goebel, 1983;Horton & Roberts, 2002;Iverson, Lange, Green, & Frazen, 2002;O'Bryant, Hilsabeck, Fisher, & McCaffrey, INTRODUCTION Although symptom validity tests may represent a ''gold standard'' for assessing effort or task engagement during neuropsychological evaluations (Vickery, Berry, Hanlon, Harris, & Orey, 2001), clinicians continue to utilize multiple sources of information when rendering decisions about patient effort (Mittenberg, Patton, Canyock, & Condit, 2002;Slick, Tan, Strauss, & Hultsch, 2004). Indicators derived from standardized neuropsychological instruments represent one additional source of data to inform decisions about the validity of test results (e.g., Axelrod, Barlow, & Paradee, 2009;Mittenberg, Azrin, Millsaps, & Heilbronner, 1993;Powell, Gfeller, Oliveri, Stanton, & Hendricks, 2004;Suhr, 2002). For example, several investigators have explored the utility of Trail Making Test (TMT; Reitan & Wolfson, 1992) scores as indicators of suboptimal effort in patient and non-patient populations (Goebel, 1983;Horton & Roberts, 2002;Iverson, Lange, Green, & Frazen, 2002;O'Bryant, Hilsabeck, Fisher, & McCaffrey, 2003;Roberts & Horton, 2003;Ruffolo, Guilmette, & Willis, 2000;Trueblood & Schmidt, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Indicators derived from standardized neuropsychological instruments represent one additional source of data to inform decisions about the validity of test results (e.g., Axelrod, Barlow, & Paradee, 2009;Mittenberg, Azrin, Millsaps, & Heilbronner, 1993;Powell, Gfeller, Oliveri, Stanton, & Hendricks, 2004;Suhr, 2002). For example, several investigators have explored the utility of Trail Making Test (TMT; Reitan & Wolfson, 1992) scores as indicators of suboptimal effort in patient and non-patient populations (Goebel, 1983;Horton & Roberts, 2002;Iverson, Lange, Green, & Frazen, 2002;O'Bryant, Hilsabeck, Fisher, & McCaffrey, INTRODUCTION Although symptom validity tests may represent a ''gold standard'' for assessing effort or task engagement during neuropsychological evaluations (Vickery, Berry, Hanlon, Harris, & Orey, 2001), clinicians continue to utilize multiple sources of information when rendering decisions about patient effort (Mittenberg, Patton, Canyock, & Condit, 2002;Slick, Tan, Strauss, & Hultsch, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The first two factors are already discussed at length in the literature (see, e.g. Powell et al ., ; Winters & Ward, ). The current study gives statistical evidence for these factors, which were found across all the trials of the test.…”
Section: Discussionmentioning
confidence: 99%